Occupational stress and burnout experience among healthcare workers compounded by the COVID-19 pandemic in Africa: a scoping review protocol - Agyemang, George; Bema, Yaa; Eturu, Deborah Aba; Bawontuo, Vitalis; Kuupiel, Desmond (Systematic reviews, 2023)
Background The emergence of coronavirus disease 2019 (COVID-19) pandemic has brought an unprecedented burden on health systems and personnel globally. This pandemic potentially can result in increased frequency of stress and burnout experienced among healthcare workers (HCWs), especially in lower-and-middle-income countries with inadequate health professionals, yet little is known about their experience. This study aims to describe the range of research evidence on occupational stress and/burnout among HCWs compounded by the COVID-19 pandemic in Africa, as well as identify research gaps for further investigations to inform health policy decisions towards stress and/burnout reduction in this era and when a future pandemic occurs. Method Arksey and O’Malley’s methodological framework will be used to guide this scoping review. Literature searches will be conducted in PubMed, CINAHL, SCOPUS, Web of Science, Science Direct, and Google Scholar for relevant articles published in any language from January 2020 to the last search date. The literature search strategy will include keywords and Boolean and medical subject heading terms. This study will include peer-reviewed papers about Africa, with a focus on stress and burnout among HCWs in the COVID-19 era. In addition to the database searches, we will manually search the reference list of included articles as well as the World Health Organization’s website for relevant papers. Using the inclusion criteria as a guide, two reviewers will independently screen the abstracts and full-text articles. A narrative synthesis will be conducted, and a summary of the findings reported. Discussion This study will highlight the range of literature HCWs’ experience of stress and/or burnout including the prevalence, associated factors, interventions/coping strategies, and reported effects on healthcare services during the COVID-19 era in Africa. This study’s findings will be relevant to inform healthcare managers plan to mitigate stress and/or burnout as well prepare for such future pandemics. This study’s findings will be disseminated in a peer-review journal, scientific conference, academic and research platforms, and social media.